2020
DOI: 10.3389/fphar.2020.00244
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Identity of Commercial Herbs From a Cambodian Market Using DNA Barcoding

Abstract: In Cambodia, medicinal plants are often used to treat various illnesses. However, the identities of many medicinal plants remain unknown. In this study, we collected 50 types of traditional Cambodian medicinal plants that could not be identified by their appearance from a domestic market. We utilized the DNA barcoding technique, combined with the literature survey, to trace their identities. In the end, 33 species were identified at the species level and 7 species were identified at the genus level. The ethnop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although surveys of wild edible plants and fungi sold in Southeast Asia are rare, some research effort has been put into studying the socioeconomic aspects of “green” open markets in general [ 44 – 47 ] as well as the contamination of plants with heavy metals [ 48 ] or parasites and pathogens [ 49 – 51 ]. Some studies from Southeast Asia performed in open air markets concern plant genetic resources from a single species, genus or family; the identification of the main cultivated plants (e.g., [ 52 – 56 ]); or medicinal plants [ 24 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although surveys of wild edible plants and fungi sold in Southeast Asia are rare, some research effort has been put into studying the socioeconomic aspects of “green” open markets in general [ 44 – 47 ] as well as the contamination of plants with heavy metals [ 48 ] or parasites and pathogens [ 49 – 51 ]. Some studies from Southeast Asia performed in open air markets concern plant genetic resources from a single species, genus or family; the identification of the main cultivated plants (e.g., [ 52 – 56 ]); or medicinal plants [ 24 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the 19 species with existing DNA barcodes and sequences, we expanded the available data by generating additional DNA sequences using a broader array of DNA barcoding markers. According to the literature, some DNA barcodes were accessible for the following species: viz; R. serpentina ; trnL-trnF, ITS2, matK, rbcL and trnL (Eurlings et al (2013); Cahyaningsih, et al (2022); C. nagbettai ; rbcL, matK, psbA-trnH, rpoC, rpoB, psbKpsbI, atpF-atpH and RPB2 (Kurian, et al (2020); (Table 1); O. indicum ; ITS2, psbA-trnH (Cui, et al (2020); G. indica ; rbcL, ITS, psbA-trnHf, RpoB-trnCGAR, Matk (Seethapathy et al 2018); C. circinalis ; ITS2 (Gao, et al (2010); S. roxburghii ; ITS1 and ITS2; psbM, rbcL, psbH, rpoC2 (Osathanunkul, et al (2021); H. parviflora; MatK, rbcL (data unpublished); V. chinensis; rbc However, in our study, we developed additional markers beyond those that currently exist. We observed that certain existing markers were not amplified in our samples, possibly due to sequence mixing, as evidenced in species such as R. serpentina, G. indica, C. circinalis, S. roxburghii , and P. santalinus (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The stems of Leea manillensis are being sold as a commercial herb in the domestic market of Cambodia (Cui et al 2020).…”
Section: Economic Importancementioning
confidence: 99%